Penerapan PSAK Syariah Terhadap Penyajian Sukuk Dalam Pelaporan Keuangan pada Bank Syariah Indonesia - Adha Sagita Sari; Vanny Rezky Pratiwi; Sintia Intan Nuraini; Megania Kharisma (Indo Publishing, 2025)
ABSTRACT The development of Islamic banking in Indonesia has led to the increasing use of sharia-compliant financial instruments, particularly sukuk, both as investment instruments and funding sources. Bank Syariah Indonesia (BSI), as the largest Islamic bank in Indonesia, plays a strategic role in managing and reporting sukuk, making compliance with Sharia Financial Accounting Standards essential. This study aims to analyze the presentation and disclosure of sukuk in the financial statements of Bank Syariah Indonesia and to assess their conformity with Sharia Accounting Standards, particularly PSAK 110 on Sukuk Accounting. This research adopts a descriptive qualitative approach using documentation and literature review methods. Data were collected from BSI’s publicly available financial statements and annual reports and analyzed using content analysis based on the provisions of PSAK 110. The findings indicate that BSI has systematically presented sukuk as part of securities held and securities issued, while sukuk returns have been recognized in the income statement in accordance with the underlying contracts. Overall, the practices related to recognition, measurement, and presentation of sukuk are largely consistent with PSAK 110. However, the disclosure of sukuk information in the Notes to the Financial Statements remains relatively general, particularly regarding contract structures, underlying assets, fair value measurement methods, and associated risks. These results suggest opportunities to enhance the depth and transparency of sukuk disclosures in order to improve the quality of Islamic financial reporting.